The effect of crystallites on the rheological properties of microphase‐separated PVC‐PBA‐PVC triblock copolymers obtained by single electron transfer‐degenerative chain transfer living radical polymerization. Issue 1 (18th June 2014) - Calafel, I.; Muñoz, M.E.; Santamaría, A.; Boix, M.; Conde, J.I.; Pascual, B.
Abstract : Linear and nonlinear rheological properties of poly(vinyl chloride) (PVC)‐poly( n ‐butyl acrylate)‐PVC triblocks of different compositions, obtained by single electron transfer‐degenerative chain transfer living radical polymerization, are investigated, focusing on the effect of crystallites. Dynamic mechanical thermal analysis results show the existence of two glass transition temperatures, denoting microphase segregation. However, rather than phase separation, it is the presence of two types of crystals that melt at T m1 = 127 ± 0.8°C and T m2 = 185 ± 2°C, respectively, the factor that determines the rheological response of the copolymers. To the difference with PVC homopolymers, extrusion flow measurements at very low temperatures ( T = 100°C) are possible with the copolymers. A change in the viscosity‐temperature dependence is observed below and above the lowest melting temperature. Notwithstanding the microphase separation and the presence of crystallites, experiments carried out in conditions similar to industrial processing reveal a remarkable viscosity reduction for our copolymers with respect to PVC obtained by single electron transfer‐degenerative chain transfer living radical polymerization, conventional PVC, and PVC/[diethyl‐(2‐ethylhexyl) phthalate] compounds. Extrudates free of surface instabilities are obtained at low extrusion temperatures, such as 90–100°C. J. VINYL ADDIT. TECHNOL., 21:24–32, 2015. © 2014 Society of Plastics Engineers